(untitled) (Kronika Bydgoska, 2010)
The reviewed book of Tomasz Kozłowski concems the State of the prison system in Poland in the 1970’s and 1980’s. The pretext for this description was a big revolt of prisoners in Bydgoszcz in September 1981. The author presented the situation in the Bydgoszcz custody in the background of other penitentiaries, and analysed the external conditions that had a significant influence on the situation in the Polish prison system. According to Kozłowski, these conditions included mainly the bad criminal and penitentiary policy, defective prison system management, the issue of political prisoners, and the attitude of the society to public order and the judiciary organs. In his book, the author showed also the role of the Independent Self-Governing Trade Union NSZZ “Solidarność” in the suppression of the revolt in the Bydgoszcz remand prison in 1981.